Dumbwaiter in 19th century lithuanian gentry homes / Maisto keltuvas Lietuvos bajorų namuose XIX a. - Marius Daraškevičius (Mokslas: Lietuvos Ateitis, 2017)
Dumbwaiters in the nineteenth century Lithuanian gentry homes – a rare and today almost extinct engineering equipment. The aim of this research is to examine still existing and extinct dumbwaiters, to name the occurring cause of their emergence, determine the specific location in the house plan and connections to other premises and to present the operation scheme of the dumbwaiter. The research is based on in-situ sources, iconographic material, periodicals, research through comparative and synthesis methods. One dumbwaiter, four shafts without equipment, and two others have been detected and investigated with the fact of their existence. The results made it possible to present the image and functioning of dumbwaiters in the food supply system. It is expected that this study will help the new owners understand not only acquired cultural and historical value of manor houses, but also the culture of the nobility, which are adapted to the architecture and reflected the needs of the owners of everyday life culture.